Implications and Application of Maslow’s Hierarchy of Needs in Community Change Initiatives - James, Latoya Antawane (My University, 2019)
For over a century, community change initiatives (CCIs) have been used by community development professionals to improve community well-being and reverse socio- economic distress in low-income communities. CCIs are comprehensive community development efforts that seek to address all socio-economic issues simultaneously. The study posits to successfully effect community change, the scale and scope of CCIs should be limited and must address the basic needs of the community before aspiring to higher level community needs. The study employs statistical action research methods, a survey, and interviews to obtain and analyze quantitative and qualitative data. Descriptive statistics, crosstabulations, and analysis of variance were used to examine research questions and test hypotheses. This study examines public administrators’ and practitioners’ CCI experiences and perceptions, assesses the need and desire for a CCI framework that targets and builds on the achievement of lower-level community needs prior to targeting higher-level needs, and proposes a CCI framework based on Abraham Maslow’s hierarchy of needs as expounded in his theory of motivation. Research reveals a connection between individual need attainment and community well-being. The study discovers difficulties public administrators and practitioners experience with CCI development and implementation in communities in which residents’ basic needs are not met. The study finds the pressure of coping with socio-economic challenges are perceived to overwhelm residents and leave them unable to participate meaningfully in CCIs. The study further finds that the scale and scope of CCIs are perceived to strain staff and organizational infrastructure. In addition, results show a preference for a CCI that builds on the achievement of meeting basic resident needs.
INTRODUCTION 1 -- Theory 2 -- Problem Statement 2 -- Purpose Statement 3 -- Study Interest 3 -- Poverty 3 -- Socio-Economic Impact 4 -- Maslow’s Hierarchy of Needs 4 -- Project Goals and Objectives 5 -- Research Questions 5 -- Hypotheses 6 -- Research Hypothesis 1 6 -- Research Hypothesis 2 6 -- Research Hypothesis 3 6 -- Methodology Overview 7 -- Researcher 8 -- Summary 9 -- REVIEW OF LITERATURE 11 -- Overview 11 -- Maslow’s Hierarchy of Needs 12 -- Need Gratification and Society 14 -- Community Change Initiatives 17 -- People and Place 18 -- CCI in a Global World 19 -- Structures and Systems 19 -- Collaboration and Networks 22 -- Forging Relationships and Building Networks. 23 -- Social and Civic Capital 24 -- Social Capital 24 -- Civic Capital 27 -- Socio-economic Factors 27 -- Poverty (Economic Scarcity) 27 -- Social and Economic Inequity 31 -- New Public Service 32 -- Community Roles 34 -- Government’s Role 34 -- Public Administrator’s Role 35 -- Resident’s Role 36 -- Summary 36 -- METHODOLOGY 39 -- Overview 39 -- Research Questions 40 -- Hypotheses 41 -- Research Hypotheses 1 41 -- Research Hypothesis 2 41 -- Research Hypothesis 3 41 -- Project Data 41 -- Variables 42 -- Participants 42 -- Sample 43 -- Survey Instrumentation and Measures 44 -- Interview Instrumentation and Measures 47 -- Study Procedures and Statistical Analysis 49 -- Institutional Review Board Oversight 50 -- Study Limitations 50 -- FINDINGS 52 -- Overview 52 -- Respondents 53 -- Research Questions 60 -- CCI Framework Preference and HOCN Usefulness 60 -- CCI Framework Preference 60 -- HOCN Usefulness 62 -- CCI Effectiveness, Barriers, and Challenges 64 -- Effectiveness 64 -- Barriers and Challenges 69 -- Resources and Capacity 73 -- Residents 73 -- Social Capital (Social Connections, Professional Networks, and Partnerships) 80 -- Organizational Capacity 82 -- Financial Resources 84 -- Hypotheses 86 -- Research Hypothesis 1 86 -- Research Hypothesis 2 88 -- Research Hypothesis 3 89 -- Summary 90 -- DISCUSSION 92 -- Overview 92 -- Hierarchy of Community Needs Preference and Usefulness 93 -- CCI Effectiveness 95 -- Resident Engagement and Capacity 98 -- Implications for Community Change and Development 104 -- Application in Community Change 105 -- Recommendations for Future Research 108 -- Conclusion 110 -- REFERENCES 113 -- APPENDIX A: 121 -- APPENDIX B 128 -- APPENDIX C: 154 -- APPENDIX D: 156.
Keywords: Dissertations, Academic--United States; Public Administration; Community development; Economics--Sociological aspects; Maslow, Abraham H. (Abraham Harold)